Application of augmented reality navigation in oral surgery - Anna V. Lysenko; Andrei I. Yaremenko; Vladimir M. Ivanov; Anton Y. Smirnov; Аlexandr I. Lyubimov; Charles S. M. Izzard; Alina A. Prokofeva (Digital Diagnostics)
BACKGROUND: Augmented reality is a potential alternative for surgical navigation, as it can provide visualization of various anatomical structures of the maxillofacial region. We have developed a specific platform for three-dimensional model management and intraoperative augmented reality navigation for surgical procedures.